2007
DOI: 10.1359/jbmr.070724
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Chondrogenesis and Wnt Signaling in PTH-Treated Fractures

Abstract: Studies have shown that systemic PTH treatment enhanced the rate of bone repair in rodent models. However, the mechanisms through which PTH affects bone repair have not been elucidated. In these studies we show that PTH primarily enhanced the earliest stages of endochondral bone repair by increasing chondrocyte recruitment and rate of differentiation. In coordination with these cellular events, we observed an increased level of canonical Wnt-signaling in PTH-treated bones at multiple time-points across the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
179
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 42 publications
11
179
0
2
Order By: Relevance
“…(34) In addition, systemic administration of PTH can enhance bone repair in animal models by increasing callus bone volume, stimulating bone formation, and restoring mechanical competence. (7,8) A similar effect has been reported in several small studies with recombinant PTH in humans to speed fracture healing. (27,35) Although these prior results indicated that PTH could activate the bone repair process, the fact that PTHR1 and other GPCRs can each activate G s , G i , and G q GPCR signaling pathways (36) poses a challenge to identifying how the G s or G i pathways specifically regulate fracture repair.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…(34) In addition, systemic administration of PTH can enhance bone repair in animal models by increasing callus bone volume, stimulating bone formation, and restoring mechanical competence. (7,8) A similar effect has been reported in several small studies with recombinant PTH in humans to speed fracture healing. (27,35) Although these prior results indicated that PTH could activate the bone repair process, the fact that PTHR1 and other GPCRs can each activate G s , G i , and G q GPCR signaling pathways (36) poses a challenge to identifying how the G s or G i pathways specifically regulate fracture repair.…”
Section: Discussionsupporting
confidence: 70%
“…We focused our assessments on days 10 and 28 because the peak of osteogenesis occurs between 10 to 14 days after fracture and because cartilage replacement with bone in the callus to bridge the fracture gap is usually completed by 28 days. (8,23) mCT imaging demonstrated that the bone fracture gap was bridged by bony tissue by day 28 ( Fig. 2A, Supporting Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Cancellous bone repair of the proximal tibia is caused by endochondral ossification (Tsuchie et al 2011), and when cartilage tissues combine after wiring, it seems that bone union is accelerated more in the PTH treated group. Recently, some reports stated that the effect of accelerated bone union by intermittent PTH administration was related to the accelerated formation of cartilage tissue (Nakazawa et al 2005;Kakar et al 2007;Kaback et al 2008). However, Sox9 expression, which is involved in the differentiation of cartilage tissue, was not accelerated at all time points.…”
Section: Discussionmentioning
confidence: 99%